A study of selected tutorial centers in talayan village in Quezon City - Beltran, Rosario R. (Manila : National University, 2006)
The study underscore the importance and prominence played by tutoring in the academic and total growth and the development of the learner.
Title Page -- Approval Sheet -- Acknowledgement -- List of Tables -- Abstract -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.